Pembagian Harta Warisan yang Sudah Tidak Jelas Keberadaan Tirkahnya Menurut Hukum Islam - Gadis Ranti (Fakultas Hukum Universitas Mulawarman, 2010)
The Islam inheritance law was part of the family’s tight law his connection with the scope of the life of humankind. The resolution and the management of the right and and the obligation someone as resulting from the existence of the legal incident because of the death someone was arranged by this law. The Islamic Law wanted the distributon og the legacy must be in accordance with the existence its tirkah, it means what was left by the heir after being reduced with the heir’s rights that must be given precedence to so that became the legacy and must be distibuted to his heir. The problem was often of the legacy just will be distributed after the existence of the lawsuit from the heir in a period of that for quite a long time after the heir died, in this case the existence of tirkah from the heir has been again unclear.